2014
DOI: 10.1186/2190-4715-26-5
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and mapping of plant phenological stages as bio-meteorological indicators for climate change

Abstract: . These shifts were stronger in Hesse (8 days) than in Germany (6 days). As winter phases tend to shift towards the end of the year, a prolongation of the vegetation period of up to 3 weeks was observed. More than 70% of the phases were correlated with air temperature by r ≥ 0.5, more than 50% even by r ≥ 0.7. Since the 1990s, phenological shifts and regional differences in phase onsets amplified. In many cases, the shifts between 2071 to 2100 and 1961 to 1990 are expected to be at least twice as high as those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 50 publications
(50 reference statements)
2
23
0
Order By: Relevance
“…Máguas et al 2011), one would expect them to respond to climatic variables by adjusting their phenological phases (i.e. the timing of phenological events), as had been previously demonstrated (Seghieri et al 2012;Schröder et al 2014). The abovementioned findings corroborate our observations that A. longifolia displayed different phenological timings in a mesic and in a xeric climate (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Máguas et al 2011), one would expect them to respond to climatic variables by adjusting their phenological phases (i.e. the timing of phenological events), as had been previously demonstrated (Seghieri et al 2012;Schröder et al 2014). The abovementioned findings corroborate our observations that A. longifolia displayed different phenological timings in a mesic and in a xeric climate (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The shifts in phenological development identified for the projection periods in the current study are comparable to those reported by other studies for European conditions [ 15 , 34 ]. Schröder et al [ 34 ], for instance, found an advancement of up to 10 days of phenological stages in the first half year, based on simulations by 10 climate models for the period 2031–60 (temperature projection +3.7 °C in 2100) for Hessen, Germany.…”
Section: Discussionsupporting
confidence: 90%
“…To obtain a statistical forecast of maize planting dates and yields in the future, simulated weather data could be used as model input, as in Schröder et al. () for phenology and Ewert et al. () for yields.…”
Section: Discussionmentioning
confidence: 99%